Solid Self-Microemulsifying Drug Delivery Systems (S-SMEDDS): Advances in Oral Bioavailability Enhancement - Kansara, Vatsal; Rathi, Sanjesh; Singh, Shubham (Journal of Neonatal Surgery, 2025)
The oral delivery of poorly soluble drugs remains a major challenge in pharmaceutical development due to limited dissolution and low systemic availability, particularly for compounds belonging to Biopharmaceutics Classification System (BCS) Class II and IV. Lipid-based drug delivery systems, especially Self-Microemulsifying Drug Delivery Systems (SMEDDS), have shown considerable potential in enhancing solubilization and absorption through spontaneous formation of fine emulsions in the gastrointestinal environment. However, conventional liquid SMEDDS suffer from limitations such as instability, leakage, and precipitation upon dilution, restricting their practical application. Solid Self-Microemulsifying Drug Delivery Systems (S-SMEDDS) have emerged as an advanced alternative, integrating the advantages of lipid-based formulations with the stability and convenience of solid dosage forms. Upon dispersion, S-SMEDDS rapidly reconstitute into nano-sized microemulsions, improving drug dissolution, permeability, and bioavailability. This review comprehensively discusses formulation strategies, excipient selection, and solidification techniques involved in the development of S-SMEDDS. The mechanisms of bioavailability enhancement, including improved solubilization, increased surface area, lymphatic transport, and inhibition of efflux transporters, are critically analyzed. Recent advances such as polymer-based and supersaturable systems, along with lipid–polymer hybrid approaches, are highlighted for their role in maintaining supersaturation and preventing drug precipitation. The application of Quality by Design (QbD) principles for systematic optimization and robust product development is also emphasized. Overall, S-SMEDDS represent a promising and versatile platform for enhancing oral bioavailability, with significant potential for future pharmaceutical innovation and commercialization..